2009
DOI: 10.2172/1043481
|View full text |Cite
|
Sign up to set email alerts
|

Complete EOS for PBX 9502

Abstract: PBX 9502 is an insensitive plastic-bonded explosive based on triaminotrinitrobenzene (TATB). A complete equation of state (BOS) is constructed for unreacted PBX 9502 suitable for reactive burn models, i.e., high pre~sure regime in which material strength is unimportant. The PBX BOS is composed of two parts: a complete BOS for TATB and a porosity model which allows for variations in the initial PBX density. The TATB BOS is based on a cold curve and a thermal model for lattice vibrations. The heat capacity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…EOSs are Shaw tables fit to experimental data for products and Mie-Grüneisen EOS for reactants for both PBX 9501 [10] and PBX 9502 [11]. A porosity model (xRage ramp) can be used to account for thermal expansion on initial density for calibrations at -55, 23, 75 °C.…”
Section: Surf/surfplusmentioning
confidence: 99%
See 1 more Smart Citation
“…EOSs are Shaw tables fit to experimental data for products and Mie-Grüneisen EOS for reactants for both PBX 9501 [10] and PBX 9502 [11]. A porosity model (xRage ramp) can be used to account for thermal expansion on initial density for calibrations at -55, 23, 75 °C.…”
Section: Surf/surfplusmentioning
confidence: 99%
“…The SURF, SURFplus simulations used Sesame tables constructed for the reactants and products based on a long time effort for modeling high explosive equations of state [11,67,69]. The AWSD simulations used the Davis reactants and products equations of state [15].…”
Section: Simulation Setupmentioning
confidence: 99%
“…Determination of the Hugoniot of the insensitive PBX 9502 explosive (95% TATB and 5% Kel-F 800 plasticizer) in a wide pressure range has shown that the data are divided into two groups [12,13]. At the shock-wave amplitude p less than p CJ , the results correspond to the Hugoniot of the inert composition.…”
Section: Determination Of the Hugoniots Of The Emulsion Matrixmentioning
confidence: 99%
“…Hence accurate equations of state are needed for the reactants and products of the PBX. The one we are using is described in (Menikoff 2009).…”
Section: -P6 New Models and Hydrocodes For Shock Wave Processesmentioning
confidence: 99%